Comparison of Functional Outcomes After Using Hamstring Graft Versus Peroneus Longus Graft Reconstruction in Patients Having Anterior Cruciate Ligament Injury - Hussain, Sadam; Kamran Saddiqui, Hafiz Muhammad; Fatima, Areej; Safdar, Sohail (Biological and Clinical Sciences Research Journal, 2025)
Anterior cruciate ligament (ACL) reconstruction is a commonly performed orthopedic procedure, with autologous grafts, such as hamstring and peroneus longus tendons, widely used. Emerging evidence suggests that the peroneus longus tendon may offer comparable or superior functional outcomes with minimal donor-site morbidity, yet limited comparative data are available in the Pakistani population. Objective: To compare the functional outcomes of ACL reconstruction using hamstring tendon grafts versus peroneus longus tendon grafts, assessed by the International Knee Documentation Committee (IKDC) score at three months postoperatively. Methods: A randomized controlled trial was conducted in the Department of Orthopaedic Surgery at Nishtar Hospital, Multan, from 15 February to 15 May 2025, enrolling 78 patients aged 20–50 years with isolated ACL injuries. Participants were randomized into two equal groups: Group A underwent ACL reconstruction using a hamstring tendon autograft, while Group B received an autograft from the peroneus longus tendon. Standardized postoperative rehabilitation was followed. Functional outcomes were assessed using the IKDC score at three months. Data were analyzed using SPSS version 22, with independent t-tests and stratified analyses to control for effect modifiers. A p-value < 0.05 was considered statistically significant. Results: The mean IKDC score was significantly higher in the peroneus longus group (83.1 ± 5.8) compared with the hamstring group (78.6 ± 6.9) (p < 0.01). Stratified analyses demonstrated consistently higher IKDC scores across age groups, gender, residence, and socioeconomic strata, with no subgroup favoring the hamstring graft. Baseline demographic and clinical characteristics were comparable between the groups. Conclusion: Peroneus longus autograft demonstrated superior early postoperative functional outcomes compared with the hamstring autograft. These findings support the use of the peroneus longus tendon as a reliable and effective alternative for ACL reconstruction in the Pakistani population.